Investigation of geometric modifications in T-type micromixers for enhanced microfluidic mixing and ZIF-8 synthesis - Tao Peng; Jinghao Liang; Xueling Zhang; Lei Chen; Yanlin Chen; Jun Qiang; Shuai Yuan (Results in Engineering)
Adequate mixing in microfluidic devices is essential for chemical and biological processes but is often limited by laminar flow conditions with diffusion-dominated mechanisms. We developed a passive micromixer with engineered structural features optimized for synthesizing zeolite imidazolate framework-8 (ZIF-8). The device combines a zigzag channel geometry with gear-shaped lateral walls and bullet-shaped flow obstacles, creating sequential flow perturbations that enhance chaotic advection. Experimental validation demonstrates an improvement in mixing efficiency across Reynolds numbers of 1–100 compared to other designs. The investigation of precursor molar ratios and flow rates revealed direct correlations between mixing performance and ZIF-8 particle size. The integrated structural features enable precise size control of ZIF-8 crystals (400 –1200 nm) by modulating interfacial shear rates during nucleation. This research advances the simple synthesis of bioactive MOFs, offering a sustainable strategy for designing stimuli-responsive drug delivery systems and applications in biosensing.